PUTUSAN VERSTEK PADA PERKARA PERCERAIAN DI PENGADILAN AGAMA PAMEKASAN - Eka Susylawati; Moh. Hasan (Research Institute and Community Engagement of IAIN MADURA, 2011)
Ideally, in investigation of divorce case of husband and wife attend in assembly.With attendance of the spouses, judge will be more easy to strive the peace mentioned above. Ironically, in practice is sometimes wife or husband in capacities as requested / sued have never attended or if to give the authority at a advocate, the side requested / sued have never attended to conference. Pursuant to section 125 HIR to express that if sued absents to face the assembly and do not order others ones as its proxy, hence the accusation will be granted with decision the outside attending of sued ( verstek decision). From result of research obtained by conclusion that is; First, which cause to be requested / to be sued never absents at divorce case raised by applicant / plaintiff so that resulting the verstek decision in Religion Justice of Pamekasan, for example: because shame, so that the session will take place quickly, because sued / requested is shy and or fear to deal with trial, and there is still some of village headman and or modin still have a notion, society in a countryside must inform if they will divorce. Judge of Religion Justice of Pamekasan assess the evidence appliances raised by applicant / plaintiff in divorce case decided by verstek guiding at HIR and also regulation of other constitutions. In the verdict of divorce case, judge council of Religion Justice of Pamekasan only relates at evidence appliance raised by plaintiff / applicant.